2019
DOI: 10.1538/expanim.18-0100
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between blood coagulability in the intra-atrial and peripheral regions during the acute phase after rapid atrial pacing

Abstract: The changes in intra-atrial blood coagulability of acute phase after development of atrial fibrillation (AF) have not been elucidated in human. In the present study, blood coagulability were examined in the intra-atrial and peripheral regions during the acute phase after development of rapid atrial pacing (RAP) in experimentally created model dog similar to AF, using Total Thrombus-formation Analysis System (T-TAS) that is capable of comprehensively evaluating thrombogenicity in the bloodstream in the microvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The time to initial clot formation (AR-chip T10) of blood collected from the right atrium and the occlusion time (OT) of both AR-and PL-chips were significantly shorter after 30 min of pacing compared to baseline. In contrast, no significant changes were observed in contemporaneous peripheral blood samples (31).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The time to initial clot formation (AR-chip T10) of blood collected from the right atrium and the occlusion time (OT) of both AR-and PL-chips were significantly shorter after 30 min of pacing compared to baseline. In contrast, no significant changes were observed in contemporaneous peripheral blood samples (31).…”
Section: Introductionmentioning
confidence: 69%
“…This study also assessed the effect of aspirin in 3 dogs and found that the PL-chip assay, but not the AR-chip assay, was affected by antiplatelet therapy (29). In two related experimental studies of atrial fibrillation induced by rapid atrial pacing, the T-TAS was used to evaluate the propensity of atrial thrombus development (30,31). The time to initial clot formation (AR-chip T10) of blood collected from the right atrium and the occlusion time (OT) of both AR-and PL-chips were significantly shorter after 30 min of pacing compared to baseline.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports of experimental models of rapid pacing‐induced atrial fibrillation (AF) in dogs were considered relevant to the PECO question. Two reports comparing the coagulability of blood sampled from the right atrium to that of peripheral blood showed evidence of hypercoagulability in atrial, but not peripheral, blood after induction of AF 138,139 . Another report demonstrated decreased trans‐mitral and left atrial appendage flow velocities during AF and following conversion to sinus rhythm compared to baseline measurements; this blood stasis may predispose to thrombosis 140 .…”
Section: Peco Question: Cardiac Arrhythmias (Dogs)mentioning
confidence: 99%
“…Two reports comparing the coagulability of blood sampled from the right atrium to that of peripheral blood showed evidence of hypercoagulability in atrial, but not peripheral, blood after induction of AF. 138,139 Another report demonstrated decreased trans-mitral and left atrial appendage flow velocities during AF and following conversion to sinus rhythm compared to baseline measurements; this blood stasis may predispose to thrombosis. 140 Induced AF in dogs also upregulates gene expression for some procoagulant mediators.…”
Section: Evidence Summarymentioning
confidence: 99%
“…7,14,20 The T-TAS has also been used in the evaluation of a canine bleeding disorder 8 and in a canine model of atrial fibrillation. 17,18 However, the T-TAS has not been evaluated in detail in healthy dogs nor used to test the ability of the analyzer to detect inhibition with in vivo or in vitro drugs in dogs.…”
mentioning
confidence: 99%